Downmodulation of Vaccine-Induced Immunity and Protection against the Intracellular Bacterium Francisella tularensis by the Inhibitory Receptor FcγRIIB - Brian J. Franz; Ying Li; Constantine Bitsaktsis; Bibiana V. Iglesias; Giang Pham; Raju Sunagar; Sudeep Kumar; Edmund J. Gosselin (Journal of Immunology Research)
Fc gamma receptor IIB (FcγRIIB) is the only Fc gamma receptor (FcγR) which negatively regulates the immune response, when engaged by antigen- (Ag-) antibody (Ab) complexes. Thus, the generation of Ag-specific IgG in response to infection or immunization has the potential to downmodulate immune protection against infection. Therefore, we sought to determine the impact of FcγRIIB on immune protection against Francisella tularensis (Ft), a Category A biothreat agent. We utilized inactivated Ft (iFt) as an immunogen. Naïve and iFt-immunized FcγRIIB knockout (KO) or wildtype (WT) mice were challenged with Ft-live vaccine strain (LVS). While no significant difference in survival between naïve FcγRIIB KO versus WT mice was observed, iFt-immunized FcγRIIB KO mice were significantly better protected than iFt-immunized WT mice. Ft-specific IgA in serum and bronchial alveolar lavage, as well as IFN-γ, IL-10, and TNF-α production by splenocytes harvested from iFt-immunized FcγRIIB KO, were also significantly elevated. In addition, iFt-immunized FcγRIIB KO mice exhibited a reduction in proinflammatory cytokine levels in vivo at 5 days after challenge, which correlates with increased survival following Ft-LVS challenge in published studies. Thus, these studies demonstrate for the first time the ability of FcγRIIB to regulate vaccine-induced IgA production and downmodulate immunity and protection. The immune mechanisms behind the above observations and their potential impact on vaccine development are discussed.